2017
DOI: 10.1111/papr.12643
|View full text |Cite
|
Sign up to set email alerts
|

Successful Control of Pain from Malignant Psoas Syndrome by Spinal Opioid with Local Anesthetic Agents

Abstract: The findings in the present cases indicate neuraxial analgesia may be of benefit, in terms of managing pain and improving functional status, in MPS patients with insufficient pain control by multimodal analgesic treatment. Physicians should consider the use of neuraxial analgesia in cases of MPS where pain is uncontrolled with multimodal analgesic treatment to provide the best possible quality of life for patients with MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…The survival of patients with MPS is considered to be very short, as demonstrated by many previous studies, and the reported median survival duration was 5.5-10.7 months after diagnosis (2,4,19,23). In the present study, patients in cases 1 and 2 died at 8 and 7 months from the time of diagnosis, respectively.…”
Section: Literature Review and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The survival of patients with MPS is considered to be very short, as demonstrated by many previous studies, and the reported median survival duration was 5.5-10.7 months after diagnosis (2,4,19,23). In the present study, patients in cases 1 and 2 died at 8 and 7 months from the time of diagnosis, respectively.…”
Section: Literature Review and Discussionsupporting
confidence: 68%
“…Recent studies have shown that rotation switching of opioids to methadone was effective for refractory neuropathic pain (6,20). Other studies reported the efficacy of intervention strategies, including epidural analgesia (9,19), injection from a psoas sheath catheter (21) or intrathecal catheter (19,22), and dorsal rhizotomy (23). Radiotherapy is occasionally adapted for both cancer-directed and palliative therapy, although its efficacy remains to be clarified (1,2,4,5).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Therapeutic options include NSAIDS, steroids, neuromodulators, opioids, local anesthetics and radiotherapy. 3,8,9 Optimal treatment of MPS should include early recognition, targeted cancer therapies (comprehended radiation therapy or surgical removal when possible), and evidence-based polymodal pharmacotherapy. 4…”
Section: Discussionmentioning
confidence: 99%
“…Some centres have shown that epidural analgesia can be effective to relieve pain to allow patients to undergo effective radiotherapy in this case 8. Various, more invasive, methods have been successful to control pain associated with MPS such as psoas sheath catheters, spinal opioids and local anaesthetics and dorsal rhizotomy 9–11…”
Section: Discussionmentioning
confidence: 99%
“…When it does occur, the iliopsoas muscle is most commonly involved 2. Pain is a common presenting feature and there are numerous ways this can be managed to improve the quality of life of affected patients 4–11. However, adequate treatment requires a firm diagnosis, and muscular metastasis can adopt a range of appearances on imaging therefore making this a difficult task as they may mimic the more common psoas abscess or haematoma 1 2 12.…”
Section: Introductionmentioning
confidence: 99%